Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Karyawan - Asyifa Dinda Ramadhanti; Epi Fitriah (Bandung Conference Series: Accountancy, 2022)
Abstract. Employee performance is a form of an employee's success in achieving the strategic goals that have been set with the expected behavior. One of the factors that can affect employee performance is the implementation of good corporate governance in the company with the principles of transparency, accountability, responsibility, independence, and fairness. The implementation of Good Corporate Governance (GCG) is a form of implementing the company's control and management process that contains policies and regulates the relationships and responsibilities between employees, creditors and stakeholders in order to realize the company's goals. This study aims to determine the application of good corporate governance, employee performance and the effect of the implementation of good corporate governance on employee performance at hospitals in Bandung. The source of data in this research is primary data. The method used is a survey method by distributing questionnaires to 50 hospital employees in Bandung. The sampling technique used by the researcher is non-probability sampling with convenience sampling technique. Statistical testing used is simple regression analysis, hypothesis testing and analysis of the coefficient of determination using SPPS 17. From the results of this study it can be concluded that the implementation of good corporate governance in hospitals in the city of Bandung has the criteria of "Good" and the performance of hospital employees in Bandung has the criteria of "Very Good", and it is known that the implementation of good corporate governance affects the performance of hospital employees in Bandung. Abstrak. Kinerja karyawan adalah bentuk keberhasilan seorang karyawan dalam mencapai tujuan strategis yang telah ditetapkan dengan perilaku yang diharapkan. Salah satu faktor yang dapat mempengaruhi kinerja karyawan adalah penerapan good corporate governance di dalam perusahaan dengan prinsip transparansi, akuntabilitas, responsibilitas, independensi, serta kewajaran dan kesetaraan. Penerapan Good Corporate Governance (GCG) adalah sebuah bentuk pelaksanaan proses pengendalian dan pengelolaan perusahaan yang berisi kebijakan serta mengatur hubungan dan tanggung jawab antara karyawan, kreditur serta para pemangku kepentingan guna mewujudkan tujuan perusahaan. Penelitian ini bertujuan untuk mengetahui penerapan good corporate governance, kinerja karyawan serta pengaruh penerapan good corporate governance terhadap kinerja karyawan pada Rumah Sakit di Kota Bandung. Sumber data dalam penelitian adalah data primer. Metode yang digunakan adalah metode survey dengan menyebarkan kuesioner kepada 50 karyawan Rumah Sakit di Kota Bandung. Teknik sampling yang digunakan oleh peneliti adalah non probability sampling dengan teknik convenience sampling. Pengujian statistik yang digunakan yaitu analisis regresi sederhana, uji hipotesis serta analisis koefisien determinasi menggunakan SPPS 17. Dari hasil penelitian ini dapat disimpulkan bahwa penerapan good corporate governance pada Rumah Sakit di Kota Bandung memiliki kriteria “Baik” dan kinerja karyawan Rumah Sakit di Kota Bandung memiliki kriteria “Sangat Baik”, serta diketahui bahwa penerapan good corporate governance berpengaruh terhadap kinerja karyawan Rumah Sakit di Kota Bandung.